2022
DOI: 10.1182/bloodadvances.2021006565
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cytogenetic characterization of myelodysplastic syndromes in cell-free DNA

Abstract: Molecular and cytogenetic studies are essential in patients with myelodysplastic syndromes (MDS) for diagnosis and prognosis. Cell-free DNA (cfDNA) analysis has been reported as a reliable non-invasive approach for detecting molecular abnormalities in MDS, however, there is limited information about cytogenetic alterations and monitoring in cfDNA. We have assessed the molecular and cytogenetic profile of a cohort of 70 patients with MDS by next-generation sequencing (NGS) using cfDNA and compared the results t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
(26 reference statements)
1
6
0
Order By: Relevance
“…Exacerbated proliferation and turn-over of the MPN clone leading to systemic DNA leakage is a plausible explanation, supported by the relationship between cfDNA and tumor burden parameters. Moreover, ineffective hematopoiesis, which characterizes cytopenic MF, could be regarded as a contributing factor, as suggested by the association between cfDNA and both anemia and thrombocytopenia, bearing comparison with the increase in cfDNA described in patients with myelodysplastic syndromes ( 49 ). In addition, pyroptosis, which is an inflammatory type of cell death mediated by inflammasome-induced Gasdermin D activation and membrane pore formation ( 26 ), might represent another potential mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…Exacerbated proliferation and turn-over of the MPN clone leading to systemic DNA leakage is a plausible explanation, supported by the relationship between cfDNA and tumor burden parameters. Moreover, ineffective hematopoiesis, which characterizes cytopenic MF, could be regarded as a contributing factor, as suggested by the association between cfDNA and both anemia and thrombocytopenia, bearing comparison with the increase in cfDNA described in patients with myelodysplastic syndromes ( 49 ). In addition, pyroptosis, which is an inflammatory type of cell death mediated by inflammasome-induced Gasdermin D activation and membrane pore formation ( 26 ), might represent another potential mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have reported that gene analysis data are very similar between blood samples and BM samples. 24,25 However, the degree of haemodilution in BM samples is vital for interpreting such data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, if diagnostic tests not affected by the BM haemodilution are developed, they will be valuable. Studies have reported that gene analysis data are very similar between blood samples and BM samples 24,25 . However, the degree of haemodilution in BM samples is vital for interpreting such data.…”
Section: Discussionmentioning
confidence: 99%
“…NGS on ctDNA and microarrays were highly concordant in detecting chromosomal alterations, and all cytogenetic aberrations detected by NGS in BM DNA were also detected on ctDNA. These results suggest that the analysis of ctDNA is a promising strategy for performing molecular characterization and monitoring of patients with MDS ( 81 ).…”
Section: Applications In Hematological Malignanciesmentioning
confidence: 93%